2016
DOI: 10.1108/oir-11-2015-0347
|View full text |Cite
|
Sign up to set email alerts
|

Social media in Latin America: deepening or bridging gaps in protest participation?

Abstract: Purpose The purpose of this paper is to explore the relationship between social media use and protest participation in Latin America. It advances two questions. First, does social media increase the chances of protest participation at the individual level, as prior research shows for advanced democracies? Second, in a region with glaring economic and political inequalities, does social media deepen or reduce the gaps in protest participation that exist among men and women, the young and the old, different soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 33 publications
3
39
1
14
Order By: Relevance
“…In Latin America, there is a wealth of literature on different factors that help to explain political participation including those on the structural conditions, individual-level factors, and the combination of the two (for example: Booth & Seligson 2009;Collier & Handlin 2009;Dunning 2009;Hawkins 2010;Moseley 2015;Moseley 2018;Piñeiro et al 2016;Valenzuela et al 2016), but we argue that leaderbased identification is one individual-level factor that has largely been omitted from this conversation or conflated with other factors.…”
Section: Leader-based Personal and Group Identitiesmentioning
confidence: 95%
“…In Latin America, there is a wealth of literature on different factors that help to explain political participation including those on the structural conditions, individual-level factors, and the combination of the two (for example: Booth & Seligson 2009;Collier & Handlin 2009;Dunning 2009;Hawkins 2010;Moseley 2015;Moseley 2018;Piñeiro et al 2016;Valenzuela et al 2016), but we argue that leaderbased identification is one individual-level factor that has largely been omitted from this conversation or conflated with other factors.…”
Section: Leader-based Personal and Group Identitiesmentioning
confidence: 95%
“…Finalmente, Valenzuela et al, (2016) estudian participación política y uso de redes sociales a través de una encuesta realizada en 17 países latinoamericanos, y señalan que si bien "las redes sociales se han convertido en un objeto de estudio prominente para la investigación sobre movimientos sociales y participación política en América Latina y otros lugares, hay vastos sectores de la población que permanecen excluidos de estas plataformas" 2 (p. 705).…”
Section: Casero-ripollésunclassified
“…En primer lugar, y en términos de objetos de estudio, sería deseable continuar con estudios que explícitamente comparen entre plataformas y entre (sub)regiones -como lo han hecho algunos trabajos relevados. En ese sentido cabe mencionar que las plataformas distan de ser universales (Valenzuela et al, 2016), y que su uso varía dependiendo de qué región se trate -como el caso de Twitter que, si bien lidera el ranking de las plataformas más estudiadas en Iberoamérica, en 2018 era utilizada por solo el 12,1% de la población latinoamericana (Statista, 2019).…”
Section: Conclusiónunclassified
“…Examining explanations for individual protest, Schussman and Soule (2005) as well as DiGrazia (2014) found that respondents interested in politics are much more likely to participate. Exploring the relationship between social media use and protest participation, Valenzuela et al (2016) showed that political interest was strongly related to protest activities. People with high political interest are more likely to guide their attention toward political information, which may then induce attitude change and contribute to further participation (Kazee 1981; Zaller 1996).…”
Section: Political Interest and Prior Political Behaviormentioning
confidence: 99%